Pemberdayaan Tokoh Adat dan Tokoh Masyarakat dalam Mencegah Konflik Antar Agama di Kabupaten Aceh Tenggara - Zulfan; Muhammad Hatta (Publikasi Indonesia, 2022)
The 1945 Constitution guarantees and protects religious freedom in Indonesia. There are several laws and regulations as implementing regulations in realizing the ideals of the constitution, such as Law no. 39 of 1999 concerning Human Rights, Law no. 1/PNPS/1965 concerning Prevention of Religious Abuse and/or Blasphemy, and Aceh Qanun No. 4 of 2016 concerning Guidelines for the Maintenance of Religious Harmony and the Establishment of Places of Worship. However, inter-religious conflicts still occur, especially in areas where there are multi-ethnic and religious groups such as Southeast Aceh Regency. Usually, the problem is triggered by a non-tolerant attitude in carrying out social life and carrying out religious rituals and beliefs between religious adherents. In Southeast Aceh district, there are four problems that often trigger disputes or conflicts between religious adherents, namely livestock farming and the sale of pigs in the community, turning on music when the call to prayer is heard, illegal construction of houses of worship, sales of liquor such as